THE USE OF L1 IN THE ENGLISH CLASSROOM - Rahmawati, Istiqomah Nur (English Education: Jurnal Tadris Bahasa Inggris, 2015)
The role of L1 in instructed English learning has been the subject of much controversy. Some teachers have the opinion that L1 may be used under certain limitations and others feel that it should not be allowed at all. The aim of this study is to investigate the effectiveness of the use L1 in promoting English learning by observing and interviewing five kindergarten teachers in Bandar Lampung. The result showed that L1 has a valuable role to play in the English classroom. Teaching English for young learners requires teachers to teach efficiently and appropriately. It indicates that the L1 gains more benefits by incorporating the students’ L1 as a learning tool and a facilitator for an efficient teaching. L1 is most useful at beginning and low levels (in this case for kindergarten students).